INFLUENCE OF PLASTIC TYPE ON COATING ADHESION DURING THE RESTORATION OF SEEDER PARTS BY GAS-DYNAMIC SPRAYING - STADNIK, MYKOLA; SHVETS, LYUDMILA; DATSIUK, DMYTRO; PANASENKO, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Gas-dynamic spraying (also known as cold gas-dynamic spraying or Cold Spray) is a modern coating technology that is becoming increasingly common due to its efficiency, environmental friendliness, and ability to work with a wide range of materials. This method is based on the acceleration of solid coating particles to supersonic speeds in a gas stream, which allows for the formation of durable coatings without significant thermal effects on the substrate. While traditionally gas-dynamic spraying has been used primarily for metal surfaces, there has been a growing interest in using this technology for plastic materials, which are widely used in the automotive, aerospace, electronics and household industries due to their lightness, corrosion resistance and cost-effectiveness.However, coating plastics is associated with a number of challenges, the main one being ensuring sufficient adhesion between the coating and the substrate. Plastics are characterized by a variety of chemical compositions, physical properties, and surface characteristics, which significantly affect the quality of adhesion to the coated layer. Parameters such as low surface energy, surface smoothness, and sensitivity to high temperatures can complicate the spraying process and lead to insufficient coating strength. At the same time, the right choice of plastic type and spraying conditions can significantly improve adhesion, opening up new opportunities for creating functional coatings, such as improving wear resistance, electrical conductivity, or decorative properties of plastic products.The purpose of this article is to systematically study the effect of plastic type on coating adhesion during gas-dynamic spraying. The paper considers various types of plastic substrates, including polyethylene, polypropylene, polyamide, and polycarbonate, which differ in their structure and properties. Particular attention is paid to the analysis of such factors as surface energy, roughness, thermal stability, and chemical nature of the material, as well as their influence on the adhesion mechanisms. The experimental part of the study includes the evaluation of adhesion strength using standard methods such as tear and peel tests, as well as microscopic analysis of the interface structure between the coating and substrate. In addition, potential methods of plastic surface preparation, such as machining, chemical etching, or plasma activation, are considered, which can contribute to improved adhesion performance. The results of this study are intended not only to expand the understanding of the interaction of plastic substrates with sputtered coatings, but also to offer practical recommendations for optimizing technological processes in industrial settings, contributing to the wider adoption of gas-dynamic sputtering in the processing of polymeric materials.
Keywords: spraying; surface layer; particle; application; coating characteristics; working environment; speed; optimization; electric power industry; seeder